Biotechnology and biology of trichoderma - Gupta, Vijai Kumar (Elsevier, 2014)
Biotechnology and Biology of Trichoderma serves as a comprehensive reference on the chemistry and biochemistry of one of the most important microbial agents, Trichoderma, and its use in an increased number of industrial bioprocesses for the synthesis of many biochemicals such as pharmaceuticals and biofuels. This book provides individuals working in the field of Trichoderma, especially biochemical engineers, biochemists and biotechnologists, important information on how these valuable fungi can contribute to the production of a wide range of products of commercial and ecological interest.